THE ROLE OF MATLAB APPLICATION FOR VISUALIZING MRI IMAGES OF THE TRIGEMINAL NERVE WITH FUSION TECHNIQUE - Indah Puspita, Mega; Sudiyono, Dr. Sudiyono, S.Pd, M.App, Sc Sudiyono (Journal of Applied Health Management and Technology, 2025)
This study addresses the crucial role of Magnetic Resonance Imaging (MRI) of the head in detecting disorders of the trigeminal nerve, particularly trigeminal neuralgia. Trigeminal neuralgia can significantly affect quality of life and is commonly observed in the elderly. However, some hospitals face limitations due to the absence of image fusion features in their MRI modalities, highlighting the need for practical alternative solutions.This study proposes the development of a MATLAB-based image fusion application as a practical alternative. The use of this application is expected to enhance visualization of the trigeminal nerve and surrounding blood vessels, particularly in hospitals whose MRI devices lack integrated image fusion capabilities. A mixed-methods approach was employed, combining qualitative analysis to describe the implementation process of image fusion using MATLAB, and quantitative analysis to compare the results with those from built-in fusion software on MRI machines.This study successfully implemented image fusion techniques using MATLAB on raw data obtained from CISS 3D and 3D TOF sequences, with a focus on visualizing the trigeminal nerve. The comparison between the fused images generated using MATLAB and those produced by the MRI system's built-in fusion software revealed significant differences. The MATLAB-based image fusion technique demonstrated a substantial contribution to improved understanding and diagnosis in medical practice, particularly in merging images from different MRI modalities. Thus, MATLAB-based fusion can be considered a relevant and progressive solution, especially for hospitals lacking access to advanced fusion technology.